PENEMBANGAN MEDIA KARTU KATA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS I SDN 03 KOTO BESAR - Aulayunita; Muhammad Subhan; Amril (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the lack of learning media in accordance with the needs of schools needed by these schools, namely learning media in Indonesian language learning. So the effort made is to develop word card learning media on the material of the five senses in class I elementary school. So that it helps teachers and students in carrying out the teaching and learning process. Research used by research is research development type of development research or in English Research and Development (R&D) Is a research method used to produce certain products, and test the effectiveness of these products needs and to test the effectiveness of products. Based on the results of trials on the development of word card learning media for the five senses in Indonesian language learning in class I SDN 03 Koto Besar, it meets the valid, practical, and effective categories. Based on the results of the assessment of the 3 validators, the five senses word card media in learning Indonesian obtained an assessment percentage of 86.66%. After being analyzed by category, namely: the content of the material gets a very valid category with a score of 21 with a percentage of 84%, the language category gets a very valid category with a score of 23 with a percentage of 92%, with a very valid category, the graphic category gets a very valid category with a score of 21 with a percentage 84% with very valid category.